A Multicomponent Microneedle Patch for the Delivery of Meloxicam for Veterinary Applications - Miranda-Muñoz, Katherine; Midkiff, Kirsten; Woessner, Alan; Afshar-Mohajer, Mahyar; Zou, Min; Pollock, Erik; Gonzalez-Nino, David; Prinz, Gary; Hutchinson, Lillian; Li, Ruohan; Kompalage, Kushan; Culbertson, Christopher T.; et al. (ACS, 2024)
This study evaluates the use of poly(vinyl alcohol), collagen, and chitosan blends for developing a microneedle patch for the delivery of meloxicam (MEL). Results confirm successful MEL encapsulation, structural integrity, and chemical stability even after ethylene oxide sterilization. Mechanical testing indicates the patch has the required properties for effective skin penetration and drug delivery, as demonstrated by load–displacement curves showing successful penetration of pig ear surfaces at 3N of normal load. In vitro imaging confirms the microneedle patch penetrates the pig’s ear cadaver skin effectively and uniformly, with histological evaluation revealing the sustained presence and gradual degradation of microneedles within the skin. Additionally, in vitro drug diffusion experiments utilizing ballistic gel suggest that microneedles commence dissolution almost immediately upon insertion into the gel, steadily releasing the drug over 24 h. Furthermore, the microneedle patch demonstrates ideal drug release capabilities, achieving nearly 100% release of meloxicam content from a single patch within 18 h. Finally, in vivo studies using pigs demonstrate the successful dissolution and transdermal drug delivery efficacy of biodegradable microneedle patches delivering meloxicam in a porcine model, with over 70% of microneedles undergoing dissolution after 3 days. While low detectable meloxicam concentrations were observed in the bloodstream, high levels were detected in the ear tissue, confirming the release and diffusion of the drug from microneedles. This work highlights the potential of microneedle patches for controlled drug release in veterinary applications.